Tracing the Phonetic Space of Prosodic Focus Marking - Roessig, Simon; Winter, Bodo; Mücke, Doris (Frontiers in Artificial Intelligence, 2022)
Focus is known to be expressed by a wide range of phonetic cues but only a few studies have explicitly compared different phonetic variables within the same experiment. Therefore, we presented results from an analysis of 19 phonetic variables conducted on a data set of the German language that comprises the opposition of unaccented (background) vs. accented (in focus), as well as different focus types with the nuclear accent on the same syllable (broad, narrow, and contrastive focus). The phonetic variables are measures of the acoustic and articulographic signals of a target syllable. Overall, our results provide the highest number of reliable effects and largest effect sizes for accentuation (unaccented vs. accented), while the differentiation of focus types with accented target syllables (broad, narrow, and contrastive focus) are more subtle. The most important phonetic variables across all conditions are measures of the fundamental frequency. The articulatory variables and their corresponding acoustic formants reveal lower tongue positions for both vowels /o, a/, and larger lip openings for the vowel /a/ under increased prosodic prominence with the strongest effects for accentuation. While duration exhibits consistent mid-ranked results for both accentuation and the differentiation of focus types, measures related to intensity are particularly important for accentuation. Furthermore, voice quality and spectral tilt are affected by accentuation but also in the differentiation of focus types. Our results confirm that focus is realized via multiple phonetic cues. Additionally, the present analysis allows a comparison of the relative importance of different measures to better understand the phonetic space of focus marking.